2015
DOI: 10.1108/jcs-07-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported care activities in a home-based intervention programme for families with multiple problems

Abstract: Purpose – The purpose of this paper is to describe the development and application of the KIPP-list of care activities. The acronym KIPP stands for Knowledge and Insight into Primary Processes. The instrument is intended as a tool for family coaches to systematically report care activities conducted in the Dutch family support programme Ten for the Future (in Dutch: Tien voor Toekomst). Design/methodology/approach – The design of the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Therefore, the findings in this study only reflect the change of the TF and CYC programmes combined. In an earlier study, Tausendfreund et al (2015) found no consistent pattern of change in emotional and behavioural problems of children that only received TF services. However, it is unclear to what extent TF services have contributed to the outcomes in this study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, the findings in this study only reflect the change of the TF and CYC programmes combined. In an earlier study, Tausendfreund et al (2015) found no consistent pattern of change in emotional and behavioural problems of children that only received TF services. However, it is unclear to what extent TF services have contributed to the outcomes in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Although whole‐family approaches show promising results (Bolt & Van der Zijden, 2021; Majoribanks & Davies, 2016; Thoburn et al, 2013), professionals often experience considerable difficulties in involving all family members in these services. Several studies have suggested care professionals experience considerable challenges in building multiple alliances with family members (Busschers & Boendermaker, 2015; Tausendfreund et al, 2015). Furthermore, professionals are often led to prioritize aspects other than child well‐being (Munro, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second could be directed at observing and measuring art therapists' behavior during sessions. A methodology that maps behavior as assessed by self-reports or external observations, based on a fixed checklist of therapeutic activities, could be used (Tausendfreund et al, 2015). Third, children's, parents', and referrers' perspectives about COAT concepts can add useful information to compare to the therapists' responses from our study (Iachini, Hock, Thomas, & Clone, 2015); this would consider the multiple perspectives on the quality of art therapy (Raban, Ure, & Waniganayake, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…What is meant by this is that little attention is paid to the child when there is a suspicion that the child's welfare is at risk, that there are cases where the child is not even spoken to or looked at. Such a lack of focus on children has been noted in the everyday practices of child protection workers (Tausendfreund et al, 2015;Alberth & Bühler-Niederberger, 2015;Ferguson, 2017;Chapeau, 2021) and especially where cases have had a fatal outcome (Fegert et al, 2010;Lundberg, 2013;Bastian, 2019). So, while the phenomenon of the invisible child is well known, there is no consensus in the literature about how often this inattention to children occurs.…”
Section: Introduction: Invisible and Inaudible Childrenmentioning
confidence: 99%